IMPLEMENTATION OF PC CONTROLLED WIRELESS VIDEO TRANSMITTING VEHICLE - P, Ramanathan (APTIKOM Publisher, 2017)
Remote PC controlled video transmitting Surveillance Car is a microcontroller based configuration whichsend serial information from PC by means of chip to the auto. This auto works as indicated by the guideline givenfrom PC. Remote transmission is behavior through transmitter to send the information and direction to the auto so itwill work as indicated by the guideline given. It transmits continuous video back to PC to screen the whereabouts ofthe auto and to see the items and the obstructions in the way. It additionally peruses an entire picture from cameraand sends it to the PC with the objective that we can surveillance through video transmission.